Formulation of Business Strategy Utilizing Environmental Analysis and Business Model to Enhance Fully Burden Operating Income (FBOI) Case Study at PT Z Indonesia - hutahaean, anton yunius; M. Riza Sutjipto; Pasaribu, Rina Djunita (International Journal of Scientific Research and Management (IJSRM), 2025)
A business strategy represents a company's comprehensive plan for attaining its projected business objectives within a defined timeframe. A critical performance indicator for a business unit is the achievement of its targeted profitability growth rate. A static or decreasing profitability rate is affected by multiple interconnected factors intrinsic to the business unit. Environmental and business model analyses furnish a holistic perspective of the business unit, facilitating the identification of business processes that can be optimized. This research aims to formulate an effective business strategy to enhance Fully Burden Operating Income case study at PT Z, a company in the oil field industry. A qualitative method with a case study approach is employed, involving Internal and external environmental analyses are conducted using the Resource-Based View framework, Value Chain Analysis, PESTEL, and Porter’s Five Forces. The results of these analyses are integrated into a SWOT/TOWS Matrix to develop strategies. Furthermore, Root Cause Analysis is integrated to identify the underlying issues hindering optimal FBOI performance within PT Z's business model. The TOWS matrix generated 40 strategies that were then combined, integrated and synthesized into 16 key strategies, then it is prioritized by priority. Those of strategies mainly focus on improvements to process efficiency and revenue enhancement, with the expected outcome of enhancing PT Z's profitability and maintaining the position as market leader within its industry. This research offers strategic business recommendations that are both comprehensive and practically applicable, with significant implications for fostering sustainable growth within the company.